The Use of Akad Salam in Pre-Order Transactions Pempek Perspective of the Yellow Book of Fathul Qorib - Maisya Hanafiah; Ahmad Misbakh Zainul Musthofa; Rizki Dwi Anggraini (Majapahit Journal of Islamic Finance and Management, 2026)
The rapid growth of digital transactions has encouraged the widespread practice of pre-order in the culinary business sector, including the trade of pempek, a traditional food from Palembang. This phenomenon demands a thorough examination from an Islamic law perspective, given that pre-order transactions bear substantial resemblance to the salam contract in Islamic jurisprudence. This study aims to analyze the conformity of pempek pre-order practices with the pillars and conditions of the salam contract according to Kitab Fathul Qorib by Imam Ibn Qasim Al-Ghazi. A descriptive-analytical qualitative method was employed, using semi-structured interviews, observation, and documentation review. The findings reveal that pempek pre-order practices are substantially similar to the salam contract, yet fail to fully satisfy its prescribed requirements. Three primary shortcomings were identified: ambiguous specification of al-muslam fih, incomplete upfront payment of ra's al-mal, and a loosely defined ajal. These deficiencies create room for gharar elements that potentially undermine the transaction's validity under Islamic law. This study recommends reforming pre-order practices and improving muamalah fiqh literacy among Muslim business actors to ensure their transactions comply with Islamic legal standards. Keywords: Salam Contract, Pempek Pre-Order, Fathul Qorib, Islamic Jurisprudence, Gharar